What is nursing in the 21st century and what does the 21st century health system require of nursing? - Scott, P. Anne (Nursing philosophy, 2014)
It is frequently claimed that nursing is vital to the safe, humane provision of health care and health service to our populations. It is also recognized however, that nursing is a costly health care resource that must be used effectively and efficiently. There is a growing recognition, from within the nursing profession, health care policy makers and society, of the need to analyse the contribution of nursing to health care and its costs. This becomes increasingly pertinent and urgent in a situation, such as that existing in Ireland, where the current financial crisis has lead to public sector employment moratoria, staff cuts and staffing deficits, combined with increased patient expectation, escalating health care costs, and a health care system restructuring and reform agenda. Such factors, increasingly common internationally, make the identification and effective use of the nursing contribution to health care an issue of international importance. This paper seeks to explore the nature of nursing and the function of the nurse within a 21st century health care system, with a focus on the Irish context. However, this analysis fits into and is relevant to the international context and discussion regarding the nursing workforce. This paper uses recent empirical studies exploring the domains of activity and focus of nursing, together with nurses perceptions of their role and work environment, in order to connect those findings with core conceptual questions about the nature and function of nursing.